Childbirth and parenting in horror texts : the marginalized and the monstrous - DiGioia, Amanda (Emerald Publishing Limited, 2017)
This book examines childbirth and parenting in horror texts. By analysing new texts, and re-analysing commonly used texts with new feminist methodology, this study provides a unique contribution to the fields of gender and horror studies. Focusing on horror fiction and film, this book reviews textual treatments of birth and motherhood, and how they differ from representations of fatherhood. Motherhood and birth are represented as revolting in several ways. Mothers in horror do not fulfil their gender role, and the neglect of motherhood by a woman is deemed horrific because it is the antithesis of Western patriarchal ideals of female identity. These mothers are unforgiven. Bad fathers, in contrast, are given moments of restoration that allow audiences or readers to feel immediate sympathy for them. Examining conception, birth, motherhood and fathers, this work provides a unique exploration of the monstrous and the marginalized within the horror genre.
Includes index.
Keywords: Horror in literature.; Mothers in literature.; Fathers in literature.; Social Science -- Gender Studies.; Horror & ghost stories.; elektronické knihy; electronic books